Study of influence of the surface-active substances concentration on releasing of praziquantel from the rectal suppository - D. M. Romanina; I. I. Berdey; V. V. Gladishev; G. P. Lisyanska (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Acne dermatosis (rosacea, perioral dermatitis, seborrheic dermatitis etc.) are one of the most actual problem in dermatology. Praziquantel is an antiparasitic medication effective towards trematodes, cestodes. Investigations developed by domestic scientists revealed antidemodicosis activity of praziquantel. Use of semisolid dosage forms for rectal administration will allow to increase its efficacy and minimize the risks of adverse reactions. On the department of technology of medications Zaporizhzhia State Medical University research of development of praziquantel rectal dosage form for therapy of acne dermatosis, complicated with demodicosis, and its technology is carried out. As a result of biopharmaceutical investigations it was determined that combination of excipients - the base (confectionary fat 60%, 10% paraffin, 30% cocoa butter) and surfactant (distilled monoglycerides) provides with the optimal praziquantel releasing. The aim of this work is study of excipient using in manufacturing of suppository (bases and surfactants) influence on the biopharmaceutical characteristics of praziquantel rectal dosage form. Investigation was carried out by the one-factors dispersive analysis with repeated observations By way of a parameter of optimization praziquantel releasing was chosen as the first step of bioavailability investigation. Praziquantel releasing from suppository was studied by the equilibrium dialysis by Kruvchinsky's method at temperature 37 ± 0,5 °С through a cellophane semipermeable membrane «Kuprofan» film using Franz diffusion cell apparatus. Ethyl alcohol was chosen as a dialysis medium considering the solubility of praziquantel. Concentration of released praziquantel after 30 minutes of the dialysis was determined by spectrophotometric analysis. As a result of biopharmaceutical investigation of praziquantel suppositories it was determined that surface-active substances (distilled monoglycerides) concentration has a statistically significant influence on its releasing from rectal dosage form. It was ascertained that 0,5% concentration of distilled monoglycerides provides with the optimal releasing of praziquantel from rectal suppositories.